A Niobium Oxyiodate Sulfate with a Strong Second‐Harmonic‐Generation Response Built by Rational Multi‐Component Design. (14th February 2019) - Tang, Hong‐Xin; Zhang, Yu‐Xiao; Zhuo, Chao; Fu, Rui‐Biao; Lin, Hua; Ma, Zu‐Ju; Wu, Xin‐Tao
Abstract: A novel niobium oxyiodate sulfate, Nb2 O3 (IO3 )2 (SO4 ), was fabricated by a rational multi‐component design under moderate hydrothermal conditions. This multi‐component design is inspired by an interesting niobium oxysulfate reaction, which opens a new door for synthetic method to effectively introduce refractory metals such as Nb into crystal structures by hydrothermal synthesis. Nb2 O3 (IO3 )2 (SO4 ) features a cube‐like topological structure with a large phase‐matching second harmonic generation (SHG) response (6×KDP), a wide transparency window (0.38–8 μm), and a high laser damage threshold (LDT) (20×AgGaS2 ). It has the highest thermostability (stable up to 580 °C under air) among reported non‐centrosymmetric (NCS) iodates and sulfates and is stable in water and even concentrated H2 SO4 . Furthermore, Nb2 O3 (IO3 )2 (SO4 ) is a unique nonlinear optical (NLO) material among iodates and sulfates, because its SHG effect is mainly caused by the MO6 units rather than the IO3 or SO4 units, which is demonstrated by density functional theory (DFT) calculations. Abstract : Sag niemals Niob : Nb2 O3 (IO3 )2 (SO4 ) wurde unter gemäßigten hydrothermalen Bedingungen synthetisiert. Der Kristall zeigt eine hohe Thermostabilität, eine ausgeprägte SHG‐Antwort, Transparenz über einen weiten Frequenzbereich sowie eine hohe Schwelle für Laserschäden.